PENGARUH PERSEPSI PENILAIAN KINERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA PEGAWAI (Studi Pada Pegawai KPP Madya Semarang) - ., Ladiman; Priyono, Bambang Suko (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study is directed to understanding the relationship between performance appraisal and compensation to employee performance through employee motivation. To answer the problem posed in this study, the data obtained from 111 employees KPP Madya Semarang by using questionnaires and census sampling method. The collected data were then analyzed using IBM SPSS analytical tools and data analysis using two stages multiple linear regression analysis. The analysis showed that: 1) the performance appraisal have positive and significant effect on work motivation; 2) compensation have positive and significant effect on work motivation; 3) performance appraisal have positive and significant effect on employee performance; 4) compensation have negative and significant effect on employee performance; and 5) work motivation have positive and significant effect on employee performance. Keywords: performance appraisal, compensation, work motivation, employee performance